Processo de trabalho no Programa Saúde da Família: um enfoque na assistência farmacêutica - Alencar, Bruno Rodrigues (2013)
This is a study about working process of Family Health Program (PSF – Programa Saúde da Família) focusing pharmaceutical services. The objectives were to understand workers meanings about pharmaceutical services of PSF, to analyze health working process focusing actions about pharmaceutical services. Else, to discuss how workers do technical assistance and technical management actions to production of care, and to identify difficulties, facilities, limits, advances and perspectives found in the pharmaceutical services. This is a qualitative research. Eleven health units of a district in the state of Bahia, Brasil. The subjects were organized in three groups: key informant (four subjects), health workers (fourteen subjects) and users (eight subjects). The technical data production was systematic observation, semi structured interview and documental analysis. The analysis method was content analysis. This study was approved by The Research and Ethics Committee of State University of Feira de Santana under the registration number 59/2012. The empiric data shows, about senses and meanings of pharmaceutical services, that subjects understand it as a health politics or government program. The agents mainly use hard and soft hard technologies. There is a predominance of management technical activities. The objects of working process were managing of medicines and disease or risk. The goals were to manage the pharmaceutical services, to educate the family health team and users, moreover taking care of them. Among the difficulties reported by subjects stood out insufficient financial resources and precarious forms of work. Furthermore, an insufficient support of pharmacists, which work on Family Health Support Core (NASF-Núcleo de Apoio à Saúde da Família), and in pharmaceutical services sector to the health units. Other difficulties were the absence of protocols and standardization of procedures about pharmaceutical services in PSF, improper disposal and steal of medicines, and inadequate structure of pharmacies. The limits were few pharmacist and many activities of workers team. Interpersonal relations and appropriate organization of medicines in the pharmacies were the facilities on the working process. The restructuring of Drug Supply Center, inclusion of medicines in Municipal List of Essential Medicines and creation of Pharmacy and Therapeutics Committee of Legal were the advances. The perspectives refer to the creation of a center of dispensing medicines and pilot project pharmacy. The working process shows disjointed between the agents, making it difficult the organization of pharmaceutical services in PSF. Moreover, noncompliance of health and professional law and difficulties in production of care on health.